Enhancing semantic web and ontologies for e-tourism. (1st October 2010) - Siricharoen, Waralak Vongdoiwang
The semantic web provides improved information access founded on the development of machine processing. E-tourism is a good applicant for semantic web because it is based on information on the internet, in sense of marketing and transaction portal. E-tourism/e-travel software is personalised inclusive for creating instantly online reservation/booking. Therefore, the success of the semantic web depends strongly on the production of ontologies. Ontologies can assist organisation, browsing, searching, and more intelligent access to information and services available online. The ideas proposed in this paper are mainly interested in the new promises afforded by ontologies in the area of knowledge management convenient to the tourism industry. The examples of ontologies description in XML-based markup language are also presented with some clarifications. The summary of useful available tourism/travel related ontologies are presented also in this paper.